Proteolytic Digestion of Purified Bovine Prothrombin: Formation of Active Fragments - Tishkoff, Garson H. (Thrombosis and Haemostasis, 1963)
Purified bovine prothrombin was subjected to proteolysis by a number of highly purified proteinases. Under specified conditions, papain and trypsin degraded prothrombin with the formation of protein fragments. These fragments were still capable of being biologically activated to thrombin by tissue thromboplastin, Factor V and calcium. Extensive enzymatic degradation of the protein moiety was achieved as evidenced by large quantities of peptide and carbohydrate rendered soluble in trichloracetic acid. Digestion of prothrombin with Nagarse, Pronase and plasmin at an identical enzyme-substrate ratio resulted in almost total inactivation of prothrombin although the extent of degradation was similar to that observed with papain. Chymotrypsin resulted in complete inactivation of clotting activities. It was also established that digested prothrombin was associated with the non-dialysable fraction. These and related observations suggest that prothrombin activity may be associated with a polypeptide fragment contained within the parent glycoprotein structure.